Potential application of liquid dye penetrants for serial number restoration on firearms. Issue 6 (2nd November 2019) - Maynard, Philip; Skinner, Kyle; Bolton, Matthew; Moret, Sébastien
Abstract: Chemical reagents for serial number restoration are designed to exploit the plastic deformation zone below the obliterated serial number. Most techniques in operational use are variants of Fry's Reagent. This technique uses toxic, corrosive chemicals and requires a skilful operator in the laboratory. Fry's Reagent can also be destructive of the firearm due to rusting. In an attempt to find a non-toxic, non-destructive alternative to Fry's Reagent, this project tested the use of liquid dye penetrants (LDPs), a non-destructive examination technique to detect cracks and imperfections used in the welding industry, for the restoration of obliterated serial numbers. Steel plates bearing an obliterated serial number with a range of obliteration depths were subjected to LDP treatment under various treatment conditions. The results using LDPs were negative for all obliteration depths and all test conditions attempted. Some of the serial numbers were subsequently restored successfully with Fry's reagent, proving that the plastic deformation zone was present on the steel plates below the obliteration. Further work to develop a non-toxic, non-destructive serial number restoration process will be undertaken.